Home quarantine during COVID-19 blunted childhood trauma-related psychiatric symptoms in Chinese college students - Hong, Wenjuan; Wang, Qiang; Hou, Qinghong; Zhao, Nan; Wang, Ruoling; Bai, Yan; Hu, Chengping; Liu, Weiqing (Frontiers in Public Health, 2023)
Background: Childhood trauma confers risks to mental health. However, little is known about whether home quarantine (HQ) during the coronavirus disease 2019 (COVID-19) pandemic exaggerated or mitigated the effect of childhood trauma on mental health. Objective: To examine the modulating effects of prior childhood traumas on the longitudinal changes of psychiatric symptoms in college students before and after HQ during the pandemic. Methods: This was a two-wave longitudinal study on the mental health of 2,887 college students before and after HQ during the COVID-19 pandemic. The relationships between the changes in the Patient Health Questionnaire-9 (PHQ-9), Symptom Checklist-90 (SCL-90), 16-item Prodromal Questionnaire (PQ-16), Childhood Trauma Questionnaire (CTQ), and Social Support Rating Scale (SSRS) scores were analyzed. Results: The students with childhood trauma showed a significantly greater decrement in psychiatric symptoms after HQ (F=17.21, 14.11, 18.87, and 17.42 for PHQ-9, PQ-16 objective and distress, and SCL-90, respectively). The correlation coefficients between the CTQ and these symptoms scales were significant at baseline (r=0.42, 0.34, 0.37, and 0.39), and decreased after HQ (r=0.17, 0.20, 0.18, and 0.19). The decrement of depressive, psychotic, and overall symptoms was positively correlated with the scores of the CTQ (r=0.08–0.27) but negatively correlated with SSRS (r=−0.08–−0.14). Multilinear regression analysis confirmed the results of the CTQ and SSRS regarding the modulation of the dynamic changes in psychiatric symptoms. A constructed structural equation model indicated that the total effects of childhood trauma on decreased psychiatric symptoms were partly mediated by lower baseline social support. Conclusions: Home quarantine during the COVID-19 pandemic could blunt the adverse effects of childhood trauma on mental health, especially for prodromal psychotic symptoms in college students. Social support from core family members may have been a significant mediating factor.